Economic analysis of solar panel at grand Indonesia - Purwoko, Tri; Lisapaly, Leonard (Institute of Computer Science (IOCS), 2025)
olar power has become one of the most potential resources in generating clean and sustainable electricity. In the last few decades, solar power technology has developed rapidly, especially in the field of solar panels. Solar panels use semiconductor materials such as silicon to convert sunlight radiation into electricity. On-grid solar power systems have become popular because they generate electricity while remaining parallel Syncron with PLN's power plants. This article discusses the economic analysis of installing solar roof panels in the PT GRAND Building Complex INDONESIA, on-grid solar power system design methodology, including building structure calculations, the area required for installing solar panels, solar panel sizes, sending controller settings, and inverter settings. investment that needs to be made and how many years will the capital be returned or Return Of Investment (ROI), Also describes the types of solar panels, namely monocrystalline, polycrystalline, and thin film solar cells (TFSC), as well as their advantages and disadvantages, The results of this study can provide a complete picture of how much profit is in installing solar roof panels, and modern solar power technology and its implementation on a large scale. Thus, this article is expected to contribute to scientists, engineers, and other stakeholders in the development and implementation of more effective and efficient solar power systems